Corona poled gelatin - Magnesium hydroxyapatite composite demonstrates osteogenicity. (2022) - Swain, Subhasmita; Patra, Abhishek; Kumari, Shubha; Praharaj, Rinmayee; Mishra, Satrujit; Rautray, Tapash
Abstract: Bone filler materials exhibit excellent biocompatibility and osteoconductivity clinically and are used to promote the repair of bone defects. These materials have attracted the attention of many researchers to investigate their effect on bone growth with electrically active properties. In the present study, bone filler composite Ca8 Mg2 (PO4 )6 (OH)2 – Gelatin (MgHA-GEL) was fabricated by freeze-drying method. The primary objective of this study was to evaluate the biomedical properties of MgHA-GEL composite after negatively poling its surface and the corresponding composite was cultured with MG63 osteoblast like cells. The in vitro results showed that the cell viability was increased after 1, 3 and 5 days of culture and along with increase in the relative expression of RUNX2, COL 1 and OCN osteogenic markers by 29%, 18% and 28% respectively. Based on the above results it can be concluded that these polarized MgHA-GEL composites have promising application for bone tissue engineering with excellent osteogenic property.